2021
DOI: 10.1186/s12889-021-12366-4
|View full text |Cite
|
Sign up to set email alerts
|

Unsuppressed viral load after intensive adherence counselling in rural eastern Uganda; a case of Kamuli district, Uganda

Abstract: Background The East Central (EC) region of Uganda has the least viral suppression rate despite having a relatively low prevalence of human immunodeficiency virus (HIV). Although the viral suppression rate in Kamuli district is higher than that observed in some of the districts in the region, the district has one of the largest populations of people living with HIV (PLHIV). We sought to examine the factors associated with viral suppression after the provision of intensive adherence counselling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…This is similar to other studies in South Africa where the nonsuppression rate was found at 15% (Lisa et al, 2014) This could be based on the fact that adults living with HIV were taking their medication, health workers were conducting adherence counseling, and drug side effects were properly managed as recommended, as statistics show that up to 85% of patients receiving care from Lira Regional Referral Hospital had a high level of adherence. This finding is in congruence with another study that revealed that barriers to VL non-suppression included forgetfulness, changes in the daily routine, side effects, and pill burden, among others (Ndikabona et al, 2021). Another study's findings also show that more than half of patients (66%) had viral suppression as of 2020 (Tomescu et al, 2022).…”
Section: Prevalence Of Hiv Rna Virological Non-suppression Among Adul...supporting
confidence: 85%
“…This is similar to other studies in South Africa where the nonsuppression rate was found at 15% (Lisa et al, 2014) This could be based on the fact that adults living with HIV were taking their medication, health workers were conducting adherence counseling, and drug side effects were properly managed as recommended, as statistics show that up to 85% of patients receiving care from Lira Regional Referral Hospital had a high level of adherence. This finding is in congruence with another study that revealed that barriers to VL non-suppression included forgetfulness, changes in the daily routine, side effects, and pill burden, among others (Ndikabona et al, 2021). Another study's findings also show that more than half of patients (66%) had viral suppression as of 2020 (Tomescu et al, 2022).…”
Section: Prevalence Of Hiv Rna Virological Non-suppression Among Adul...supporting
confidence: 85%
“…[6][7][8] Conversely, evidence from other contexts indicates that there are sub-optimal HIV-1 viral load suppression rates following the IAC program. [9][10][11][12] Informal interactions with HIV healthcare providers in the context of rural northern Uganda also indicated that some HIV-positive clients remain virally non-suppressed even after IAC. This could be attributed to the weak healthcare systems in such contexts which undermines harnessing the benefits of IAC.…”
Section: Introductionmentioning
confidence: 99%
“…A study in West Ethiopia, Northern Ethiopia, South Africa, and Nigeria also showed that viral re‐suppression rate after EAC was low 29,66–68 indicating that EAC alone may not be effective in viral load suppression without drug resistance tests. Research evidence showed that the rate of EAC sessions among individuals who had VF was not complete yielding a lower viral re‐suppression rate 65,69,70 . Enhanced adherence counseling was not effective in reversing virologically defined treatment failure for patients on long‐term ART who had no genotype tests because of the probability of having genetic mutations of the virus 63 …”
Section: Discussionmentioning
confidence: 99%
“…Research evidence showed that the rate of EAC sessions among individuals who had VF was not complete yielding a lower viral re-suppression rate. 65,69,70 Enhanced adherence counseling was not effective in reversing virologically defined treatment failure for patients on long-term ART who had no genotype tests because of the probability of having genetic mutations of the virus. 63…”
Section: Discussionmentioning
confidence: 99%